Association Between Dietary Intakes of B Vitamins in Midlife and Cognitive Impairment in Late-Life: The Singapore Chinese Health Study. (15th May 2019) - Sheng, Li-Ting; Jiang, Yi-Wen; Pan, Xiong-Fei; Feng, Lei; Yuan, Jian-Min; Pan, An; Koh, Woon-Puay
Abstract: Background: Dietary intakes of B vitamins (eg, folate) are related to cognitive function according to epidemiological studies in western countries. But prospective studies in Asian populations are scarce. This study evaluated the relationships of dietary intakes of six B vitamins in midlife with cognitive impairment in old age in a Chinese population living in Singapore. Methods: This study included 16, 948 participants from the Singapore Chinese Health Study, a population-based prospective cohort. Baseline dietary intakes of B vitamins were assessed using a validated 165-item food frequency questionnaire when the participants were aged 45–74 years (1993–1998). After an average follow-up of 20 years, cognitive function was examined using a Singapore-modified version of Mini-Mental State Examination scale in 2014–2016, and cognitive impairment was defined using education-specific cutoffs. Logistic regression models were applied to estimate the association between B vitamins and cognitive impairment. All the six B vitamins were mutually adjusted in the final model. Results: In the 2014–2016 interview, 2, 443 participants were defined as cognitive impairment. Riboflavin and folate were significantly and independently associated with cognitive impairment in a dose-dependent manner: the odds ratio (95% confidence interval) comparing the highest with the lowest quartile was 0.82 (0.69, 0.97) for riboflavin and 0.83 (0.70, 0.98) for folate (both p -trend <.05). Dietary intakes of thiamine, niacin, vitamin B-6, and B-12 were not significantly associated with risk of cognitive impairment. Conclusions: Higher dietary intakes of riboflavin and folate in midlife were associated with a lower risk of cognitive impairment in late-life in the Chinese population.